Prevalence and Patterns of Self-Medication among Undergraduate Students of National Medical College: A Cross-sectional Study - Yadav, Binod Kumar; Chaudhary, Khusboo; Dhungana, Diamond; Joshi, Aayush; Thakur, Prashant (Nepal Journal of Health Sciences, 2026)
Introduction: Self-medication refers to the use of medicines by individuals to manage symptoms or illnesses that they identify themselves without consulting a healthcare professional. In Nepal, easy access to medicines contributes to the widespread practice of self-medication. Self-medication behavior among young people may also be influenced by peer pressure. Objective: To assess the prevalence and patterns of self-medication among undergraduate medical students. Method: A descriptive cross-sectional study was conducted among undergraduate bachelor of medicine and bachelor of surgery students at National Medical College, Birgunj, from March to June 2022. The calculated sample size was 235 students. Semistructured questionnaire was used and analyzed using Microsoft Excel 2016 and statistical package for the social sciences version 26. Results: The prevalence of self-medication among students was found to be 32.8% (n = 77). The majority of respondents were male (63.4%), the most common age groups were 20-21 years (79, 33.6%) and 22-23 years (73, 31.1%). Second-year students constituted the largest group 81 (34.5%). Fever, headache and cough were common symptoms showing 39(50.6%), 36(46.8%) and 26(33.8%) respectively. Forty-nine (63.6%) participants confirmed the medication’s prescription and its expiration date. Only 19 (24.7%) had government sponsored insurance. Conclusion: Self-medication was common among undergraduate medical students. Fever, headache, and cough were the most frequently reported symptoms, while saving time and old prescriptions were the main reasons. Most students used allopathic medicines. Despite medical knowledge, some experienced adverse effects and many lacked health insurance, highlighting the need to promote rational drug use and appropriate healthcare-seeking behavior. Keywords: Fever; headache; self-medication.